THE PSYCHOLOGICAL FACTORS AFFECTING BEHAVIOR OF INDIVIDUAL BUYERS: A CASE STUDY IN GENERAL COMPANY FOR CENTRAL MARKETS OF IRAQ - Sarmad Hamza Jassim; Nagham Abbas Rasin (Scholar Express Journals, 2024)
All business companies are interested in increasing their market share by acquiring new customers, and this achieved when company able to successfully manage the behavior of individual buyers. Research identifies four psychological factors that affect the behavior of individual buyers: motivation, perception, learning, and attitudes. Research attempts to reveal the relative importance of each factor so that companies can direct their attention in a way that is appropriate to the extent of its impact on the behavior of individual buyers. It adopts a case study approach in the General Company for Central Markets of Iraq and has relied on field interviews and personal interviews of managers in company, whose number reached (52) manager, for purpose of answering the inspection lists. Research concluded that the company pays varying attention to the four psychological factors, and it recommended the necessity of achieving a state of balance and paying attention to the four factors in order to be able to reach its goals
Keywords: Behavior of Individual Buyerss; Psychological Factors; Motivation; Perception